DOI: 10.14264/uql.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

The legislative context of prejudice motivated victimisation: perceptions of police legitimacy and citizen decisions to report hate crime incidents

Abstract: Prejudice motivated crime (PMC) legislation varies across different jurisdictions in Australia. Some use criminal codes and civil codes, while other laws are based in anti-discrimination legislation. ii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…A factor analysis indicated that item (a) people in this community prefer that residents in the area are mostly Anglo Saxon IJCJ&SD 103 Online version via www.crimejusticejournal.com © 2018 7(2) and item (b) people in this community do not like having members of other ethnic groups as next door neighbours, loaded highly onto one factor. 6 For further information, see Wiedlitzka (2016). 7 We detected a partial mediation effect between property crime and identifying as an Australian citizen, indicating that being victimised by a property crime may partially explain why Australian citizenship is related to reporting crime to police.…”
Section: Police Legitimacy and Cooperationmentioning
confidence: 87%
“…A factor analysis indicated that item (a) people in this community prefer that residents in the area are mostly Anglo Saxon IJCJ&SD 103 Online version via www.crimejusticejournal.com © 2018 7(2) and item (b) people in this community do not like having members of other ethnic groups as next door neighbours, loaded highly onto one factor. 6 For further information, see Wiedlitzka (2016). 7 We detected a partial mediation effect between property crime and identifying as an Australian citizen, indicating that being victimised by a property crime may partially explain why Australian citizenship is related to reporting crime to police.…”
Section: Police Legitimacy and Cooperationmentioning
confidence: 87%
“…6. For more detailed information about the demographic variables please refer to Wiedlitzka (2016). 7.…”
Section: Notesmentioning
confidence: 99%